FLUXURILE FINANCIARE – COMPONENT DETERMINANT ÎN ESTIMAREA ACŢIUNILOR - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2009)
In the article the author argues the role of financial flows in determining the estimated value of shares, determining their specifics through a series of methods. Depending on the types and size of the estimated shares financial flows can be calculated by different techniques, financial flows representing the size of revenue generated by their assets. An important aspect in determining the estimated value of the shares is discount cash flows.